Estrategias competitivas para la exportación de camarón al mercado de Corea del Sur en 2024 según el acuerdo estratégico de cooperación económica (seca). - Carrion Abad, Byron Mikele (Machala : Universidad Técnica de Machala, 2024)
Ecuador has identified a significant advantage in its export offering that meets South Korean standards through the Strategic Economic Cooperation Agreement (SECA). Therefore, it is essential to investigate possible strategies to highlight our products in such a competitive market. This is particularly relevant for the Ecuadorian shrimp export sector to the South Korean market. Producers should focus their efforts on implementing measures that not only comply with Korean market regulations and quality standards but also highlight the unique qualities and competitive advantages of Ecuadorian shrimp. During the research, three key strategies have been identified: obtaining international quality and sustainability certifications, developing innovative products and value-added processes, and forming strategic alliances. These strategies, applicable to companies of all sizes within the sector, will facilitate access to the South Korean market and consolidate the position of Ecuadorian shrimp in that market. The research results indicate that international certifications help meet South Korean market standards, while innovation in products and processes allows for seizing new opportunities and improving the offering. Additionally, the formation of strategic alliances facilitates entry and expansion into the South Korean market, boosting the growth and sustainability of the Ecuadorian shrimp industry.
Ecuador ha identificado una ventaja significativa en su oferta exportable que cumple con los estándares de Corea del Sur a través del Acuerdo Estratégico de Cooperación Económica (SECA). Por lo tanto, es fundamental investigar las posibles estrategias para destacar nuestros productos en un mercado tan competitivo. Esto es especialmente relevante para el sector de exportación de camarón ecuatoriano al mercado surcoreano. Los productores deben enfocar sus esfuerzos en implementar medidas que no solo cumplan con las normativas y exigencias de calidad del mercado coreano, sino que también resalten las cualidades únicas y ventajas competitivas del camarón ecuatoriano. Durante la investigación se han identificado tres estrategias clave: la obtención de certificaciones internacionales de calidad y sostenibilidad, el desarrollo de productos innovadores y procesos de valor añadido, y la formación de alianzas estratégicas. Estas estrategias, aplicables a empresas de todos los tamaños dentro del sector, facilitarán el acceso al mercado surcoreano y consolidarán la posición del camarón ecuatoriano en dicho mercado. Los resultados de la investigación indican que las certificaciones internacionales ayudan a cumplir con los estándares del mercado surcoreano, mientras que la innovación en productos y procesos permite captar nuevas oportunidades y mejorar la oferta. Además, la formación de alianzas estratégicas facilita la entrada y expansión en el mercado surcoreano, potenciando el crecimiento y la sostenibilidad de la industria camaronera ecuatoriana.
Keywords: CAMARON; MERCADO; EXPORTACION; ESTRATEGIA